The Importance of Fitness Sports for Health and Prevention - Tokarski, Walter; Tosounidis, Antonis; Zarotis, George F. (Disease and Health: Research Developments Vol. 7, 2025)
The concept of health is subject to dynamic change. The World Health Organization (WHO, n.d.) defines health as a state of extensive physical, mental, and social well-being. Health is at the top of the social value hierarchies in Western industrialized countries. It enables people to actively participate in social processes. In the course of industrialization, humans have been formally educated to be sedentary. The trend towards passivity and predominantly sedentary activities during working hours has resulted in an increase in health problems in the chronic-degenerative field. Curative medicine is reaching its limits with these diseases. In order to achieve an improvement in the health situation, it is necessary to make personal lifestyles more health-oriented. The aim of this study is to provide a comprehensive inventory of the need for health and prevention through fitness sports in today's society, in order to create recommendations for action. The methodology used in this study was a review of the relevant literature. In analysing various research findings, it was discovered that essential to health promotion is preventive orientation and turning towards health instead of focusing on disease. The concept of health promotion complements the previously dominant concept of disease prevention, with the goal of increased prevention and active mobilization of all health-supporting influencing factors. The importance of health promotion is emphasized in the sense of moving away from a perspective of health education and prevention-oriented only to pathogenesis and to risks and risk factors. Health promotion includes all strategies and measures that positively influence health and this in turn also includes prevention in all its stages as well as disease treatment. There is sufficient evidence that exercise and sport have positive effects on health and well-being; this goes as far as living longer, but at least leads to a better quality of life in old age. Fitness sports providers and fitness sports consumers bring their interests into impressive harmony in this respect: weight reduction, improving physical performance, improving energy balance, improving appearance, living healthily, and sleeping better, among others, are the primary reasons for visiting a gym. Prevention through exercise and sport therefore needs to be brought more into awareness, at all levels: among politicians, among employers and employees, among families, teachers, and caregivers, and among younger and older people. Modern fitness sports can play an important and central role in this context for the future. Fitness facilities represent ideal venues for prevention in this regard. One of the most striking features of the fitness market is the permanent development and renewal of fitness sport and its framework conditions - and thus of sport in general. Last but not least, this also sets lifestyle standards that influence value schemes and health behaviour: health, body behaviour and prevention.